FSW-joined body and manufacturing method thereof
By dispersing oxides during FSW to prevent layered formation, the method enhances the strength and durability of FSW joints in age-hardenable alloys, maintaining structural integrity during solution aging treatment.
Patent Information
- Application Number
- JP2024093073
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-12
- Filing Date
- 2024-06-07
- Publication Date
- 2024-12-24
AI Technical Summary
Existing methods of fabricating layered structures using friction stir welding (FSW) result in damage at the joints when subjected to solution aging treatment due to the dispersion of oxides that remain in a layered form, leading to reduced strength.
The method involves dispersing or fragmenting oxides without leaving them in a layered form during FSW, ensuring the joints are free of voids and can withstand solution aging treatment without damage, using age-hardenable alloys like copper and aluminum alloys.
The FSW joined body maintains strength comparable to or exceeding that of the base material even after solution aging treatment, preventing joint damage and ensuring structural integrity.
Smart Images

Figure 2024178133000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an FSW joint and a method for producing the same. [Background technology]
[0002] Friction stir welding (hereinafter, FSW) is a known method of joining members. In FSW, as shown in FIG. 1, a cylindrical tool 2 having a protruding probe 6 at the tip of a shank 4 is rotated and pressed with strong force to insert the probe 6 into a joint 10a of metal members 10 (base material) to be joined, which generates frictional heat and softens the base material. At the same time, the rotational force of the tool 2 causes plastic flow around the joint of the base material and kneads the multiple metal members 10 to be integrated, while the tool 2 is moved in a specified joining direction. In this way, an FSW joint in which multiple metal members 10 are joined is obtained.
[0003] Also, an additive manufacturing method is known in which a laminated structure is formed using FSW. For example, Patent Document 1 (JP Patent No. 6587028) discloses an additive manufacturing method including the steps of arranging a metal plate material on a laminated joint (first step), heating and joining the metal plate material and the laminated joint (second step), and forming a laminated joint by processing one or more layers of metal plate material joined to the laminated joint (third step), and repeating the first to third steps until the laminated joint formed in the third step becomes a laminated structure. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6587028 Summary of the Invention
[0005] However, when an attempt was made to fabricate a mold as a laminated structure (FSW joint) using the additive manufacturing method with FSW, it was found that damage could occur along the joint when it was subjected to solution aging treatment.
[0006] The present inventors have now discovered that it is possible to provide an FSW joint that can achieve strength comparable to that of the base material after solution aging treatment by dispersing or breaking up the oxides that may remain after FSW inside the FSW joint without leaving them in layers, thereby preventing breakage at the joint when it is subjected to solution aging treatment.
[0007] Therefore, an object of the present invention is to provide an FSW joint that can avoid breakage at the joint when it is subjected to solution aging treatment and can achieve strength equivalent to that of the base material after solution aging treatment. Another object of the present invention is to provide a method for manufacturing an FSW joint that achieves strength equivalent to that of the base material without causing breakage at the joint.
[0008] According to the present invention, the following aspects are provided. [Aspect 1] A friction stir welding (FSW) joint in which a plurality of metal members are joined together by FSW, wherein oxides that may remain after FSW are dispersed or separated inside the FSW joint without remaining in a layer form. [Aspect 2] 2. The FSW joint according to embodiment 1, wherein the plurality of metal members are joined to one another without leaving any voids at the joint interface. [Aspect 3] 3. The FSW joint according to any one of the preceding claims, wherein the FSW joint is to be subjected to a solution ageing treatment. [Aspect 4] 4. The FSW joint according to any one of aspects 1 to 3, wherein each of the plurality of metal members is made of an age-hardenable alloy. [Aspect 5] 5. The FSW joint of embodiment 4, wherein the age hardenable alloy is an age hardenable copper alloy and / or an age hardenable aluminum alloy. [Aspect 6] 6. The FSW joint according to any one of aspects 1 to 5, wherein even when the joint is subjected to a solution aging treatment, the joint does not break and has a strength equal to or greater than the strength of the base materials of the metal members. [Aspect 7] The FSW joint according to any one of aspects 1 to 6, wherein the metal members are made of a beryllium copper 25 alloy (C1720 of JIS H 3130 and JIS H 3270), and the tensile strength of the joint and base material of the metal members when subjected to solution aging treatment is 1100 MPa or more. [Aspect 8] 7. The FSW joint according to any one of aspects 1 to 6, wherein the metal members are made of beryllium copper 11 alloy (C1751 of JIS H 3130), and the tensile strength of the joint and base material of the metal members is 690 MPa or more when the joint is subjected to solution aging treatment. [Aspect 9] 7. The FSW joint according to any one of aspects 1 to 6, wherein the metal members are made of extra super duralumin (A7075 of JIS H 4000), and the tensile strength of the joint and base material of the metal members when subjected to solution aging treatment is 330 MPa or more. [Aspect 10] 7. The FSW joint according to any one of aspects 1 to 6, wherein the metal members are made of extra super duralumin (A7075 of JIS H 4000), and the tensile strength of the joint and base material of the metal members is 495 MPa or more when the joint is subjected to solution aging treatment. [Aspect 11] 11. The FSW joint according to any one of aspects 1 to 10, wherein the FSW joint has an internal space as a cooling path therein. [Aspect 12] A method for manufacturing an FSW joint in which a plurality of metal members are joined together by friction stir welding (FSW), comprising the steps of: (a) placing a metal member on another metal member; (b) a step of inserting a tool into the other metal member and the metal member underneath the other metal member and performing FSW to join the metal member and the other metal member, the FSW being performed in such a way that oxides are dispersed or separated without remaining in a layer; (c) removing the surfaces of the metal members joined by the FSW by cutting to form a machined surface; (d) repeating steps (a), (b) and (c) to produce an FSW joint, wherein step (a) is performed such that another metal member is placed on the work surface; and (e) subjecting the FSW joint to a solution aging treatment; A method for producing an FSW joint, comprising: [Aspect 13] 13. The method of claim 12, wherein each of the metallic members is comprised of an age hardenable alloy. [Aspect 14] 14. The method of claim 13, wherein the age hardenable alloy is an age hardenable copper alloy and / or an age hardenable aluminum alloy. [Aspect 15] 15. The method for producing an FSW joint according to any one of aspects 12 to 14, wherein the joint of the metal members is not broken during the solution aging treatment, and the joint after the solution aging treatment has a strength equal to or greater than a strength of the base materials of the metal members. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a perspective view for conceptually explaining FSW. [Diagram 2] 1 is a photograph of an FSW joining device used in the examples. [Diagram 3] FIG. 2 is a schematic diagram for explaining the shape and dimensions of an FSW tool used in the examples. [Figure 4] 1 is a photograph of an FSW tool fixed to a holder used in an example. [Figure 5A] FIG. 5 is a close-up side view of the FSW tool shown in FIG. 4. [Figure 5B]This is a close-up photograph taken from below of the FSW tool shown in Figure 4. [Figure 6] FIG. 1 is a top view and a perspective view for explaining FSW in an embodiment. [Figure 7] FIG. 2 is a schematic diagram for explaining the orientation of an FSW joint and a test piece taken from the joint in the examples. [Figure 8A] 1 shows a cross-sectional SEM image (COMPO image) obtained for the copper beryllium FSW joint produced in Example A2 (Comparative Example). In the figure, the arrow points to the joint 10a (same below). [Figure 8B] FIG. 8B shows an EPMA oxygen mapping image of Example A2 measured over an area corresponding to the SEM image of FIG. 8A. [Figure 9A] 1 shows a cross-sectional SEM image (COMPO image) obtained for the beryllium copper FSW joint produced in Example A8 (embodiment). [Figure 9B] FIG. 9B shows an EPMA oxygen mapping image of Example A8 measured over an area corresponding to the SEM image in FIG. 9A. [Figure 10A] 1 shows a cross-sectional SEM image (COMPO image) obtained for the extra super duralumin FSW joint produced in Example B1 (Comparative Example). [Figure 10B] FIG. 10B shows an EPMA oxygen mapping image of Example B1 measured over an area corresponding to the SEM image of FIG. 10A. [Figure 11A] 1 shows a cross-sectional SEM image (COMPO image) obtained for the extra super duralumin FSW joint produced in Example B6 (embodiment). [Figure 11B] FIG. 11B shows an EPMA oxygen mapping image of Example B6 measured over an area corresponding to the SEM image in FIG. 11A. [Figure 12A] 1 shows a cross-sectional SEM image (COMPO image) obtained for the copper beryllium FSW joint produced in Example C1 (Comparative Example). [Figure 12B] FIG. 12B shows an EPMA oxygen mapping image of Example C1 measured over an area corresponding to the SEM image in FIG. 12A. [Figure 13A]1 shows a cross-sectional SEM image (COMPO image) obtained for the beryllium copper FSW joint produced in Example C2 (embodiment). [Figure 13B] FIG. 13B shows an EPMA oxygen mapping image of Example C2 measured over an area corresponding to the SEM image in FIG. 13A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] FSW joint The FSW joint of the present invention is a joint in which a plurality of metal members are joined together by friction stir welding (FSW). In the FSW joint, oxides that may remain after FSW are dispersed or separated without remaining in layers inside the FSW joint. This makes it possible to avoid breakage at the joint when subjected to solution aging treatment, and to achieve strength equivalent to that of the base material after solution aging treatment. In this specification, "without oxides remaining in layers" means that when an oxygen mapping image is obtained by performing elemental analysis by EPMA as described in the examples below on a polished cross section including the joint of the FSW joint, pixels showing a locally higher oxygen concentration than the surroundings are not observed as streaky lines with a length of 10 μm or more at a position corresponding to the joint in the EPMA oxygen mapping image.
[0011] That is, as mentioned above, when we tried to manufacture a mold as a laminated structure (FSW joint) by the additive manufacturing method using FSW, it was found that damage could occur along the joint when it was subjected to solution aging treatment. Specifically, when a mold manufactured as a laminated structure by FSW was solutionized (held at 780°C for 3 hours and then water-cooled) and then aged (held at 315°C for 3 hours and then furnace-cooled), there were cases where cracks occurred along the joint (lamination surface) between the components. As a result of the analysis, it was found that a layered oxide film remained along the joint (this is observed as black streaks in the microstructure), and that this oxide film was the starting point for the fracture along this layer. This layer is an oxide film formed on the surface that became overheated during FSW and / or an oxide film that was originally present on the surface of the components that was broken down during FSW and kneaded into the joint in a layer, and similar layers are observed not only in age-hardenable alloys but also in non-age-hardenable alloys. However, no fracture along this layer has been reported in non-age hardenable alloys, and the inventors have not confirmed fracture during FSW (i.e., before solution treatment) of age hardenable alloys in their experiments. Regarding the phenomenon in which cracks are confirmed along this layer during solution aging treatment as in this example, it was determined that although the bonding strength of this layer (although weaker than that of the base material) is not so weak that cracks are generated or propagated by the stress generated in the joint by FSW, it may be the cause of crack generation or propagation due to thermal shock during solution treatment or internal stress associated with crystal distortion generated during aging. Thus, the inventors have found that the oxide film that existed beforehand on the surface of the components and / or formed by the temperature rise during joining is distributed in a layer at the site where fracture occurs during solution aging, and fracture occurs along this layered oxide film. In response to this problem, in the present invention, FSW is performed so as to disperse or break the oxides without leaving them in a layered state, and thus it is possible to provide an FSW joint that does not break even after solution aging and has strength comparable to that of the base material.In this regard, although it is inevitable that oxide films generated by heating the surfaces of non-joined components during FSW and / or oxide films originally existing on the surfaces of components remain and are kneaded into the components during FSW, there have been occasional cases where the oxide film (which would otherwise remain as black streaks along the joint) has moved up and down the joint by adjusting the FSW conditions. In this way, by selecting the joining conditions, it is possible to break up or disperse the oxide film that may remain as black streaks, thereby preventing damage to the joint during solution aging.
[0012] The FSW joint can be manufactured using either a non-aging alloy or an age-hardening alloy. In particular, the age-hardening alloy can obtain the desired tempering characteristics (e.g., high strength) by undergoing solution treatment and aging treatment, and is expected to improve the performance of the equipment to which it is applied. Therefore, it is preferable that the FSW joint according to the present invention does not break at the joint of the metal members even when it is subjected to solution aging treatment, and the joint has a strength equal to or greater than the strength of the base material of the metal members. The solution aging treatment will be described in the manufacturing method described later.
[0013] In the FSW joint according to the present invention, when an age-hardenable alloy (e.g., age-hardenable copper alloy and / or age-hardenable aluminum alloy) is used, cracks do not occur in the joint even after solution treatment and aging treatment because the oxide residual layer, which has a weak joint strength, is broken or dispersed by the technology of the present invention. Therefore, it is preferable that each of the metal members of the FSW joint is composed of an age-hardenable alloy (e.g., age-hardenable copper alloy and / or age-hardenable aluminum alloy). Examples of the age-hardenable copper alloy include CuBe-based alloys, CuNiSn-based alloys, CuNiSi-based alloys, TiCu-based alloys, CrCu-based alloys, CrZrCu-based alloys, and combinations thereof. Specific examples of the age-hardenable copper alloys include beryllium copper alloys such as C1720, C1700, and C1751, and combinations thereof. Examples of the age-hardenable aluminum alloys include A2000-based, A6000-based, and A7000-based aluminum alloys, and combinations thereof.
[0014] In a preferred embodiment of the present invention, the metal member may be made of beryllium copper 25 alloy (a plate or bar of C1720 of JIS H 3130 and JIS H 3270, or a forged material of the same chemical composition as C1720). The beryllium copper 25 alloy is advantageous in that it has the highest tensile strength among age-hardenable copper alloys. In this embodiment, the tensile strength of the joint and base material of the metal members (beryllium copper 25 alloy) constituting the FSW joint body when subjected to solution aging treatment is preferably 1100 MPa or more, more preferably 1130 MPa or more. The tensile strength of the base material and joint of the FSW joint body can be measured by preparing a test piece (based on ASTM E8 Specimen 4) with the shape and dimensions (units in the figure: mm) shown in FIG. 7 so that the joint is located at the center of the longitudinal direction of the test piece, and performing a tensile test on the test piece according to a procedure based on ASTM E8.
[0015] According to another preferred embodiment of the present invention, the metal member may be made of beryllium copper 11 alloy (a plate material of C1751 of JIS H 3130, or a bar material or forging material having the same chemical composition as C1751). The beryllium copper 11 alloy is advantageous in that the base material exhibits a high thermal conductivity of at least 230 W / mK and a tensile strength of at least 690 MPa when subjected to solution aging treatment, particularly in terms of assuming application to a die material. In this embodiment, the tensile strength of the joint and base material of the metal members constituting the FSW joint is preferably 690 MPa or more, more preferably 760 MPa or more, when subjected to solution aging treatment. The method for measuring the tensile strength of the base material and joint of the FSW joint is as described above.
[0016] According to yet another preferred embodiment of the present invention, the metal members can be made of extra super duralumin (A7075 of JIS H 4000). Extra super duralumin is advantageous in that it has a particularly high tensile strength among aluminum alloys. In this embodiment, the tensile strength of the joint and base material of the metal members constituting the FSW joint when subjected to solution aging treatment is preferably 330 MPa or more, and more preferably 495 MPa or more. The method for measuring the tensile strength of the base material and joint of the FSW joint is as described above.
[0017] As described above, the FSW joint is a structure in which a plurality of metal members are joined together by FSW. The shape of the metal members used in the FSW joint is not particularly limited, but it is preferable to use metal plates. The number of metal members (preferably metal plates) used in the FSW joint is not particularly limited as long as it is 2 or more, and may be 10 or more, 50 or more, or 100 or more. It is sufficient to use the number necessary to obtain an FSW joint of a predetermined shape and size to be manufactured. This is because in the additive manufacturing method using FSW, any number of layers can be stacked by repeating FSW joining.
[0018] It is preferable that the multiple metal members are joined together without leaving any voids at the joint interface. The absence of voids at the joint interface can significantly increase the tensile strength of the joint and base material of the metal members constituting the FSW joint when subjected to solution aging treatment. The presence or absence of voids at the joint interface can be evaluated by cutting the FSW joint perpendicular to the joint surface and subjecting it to a dye penetrant test described in JIS Z 2343-1 "Nondestructive testing - Penetrant testing".
[0019] It is preferable that the FSW joint has an internal space as a cooling path inside. Since the FSW joint having an internal space as a cooling path inside can have a complex internal structure, it can be said that it is suitable to manufacture it by additive manufacturing using FSW. In fact, the present inventors have attempted to manufacture a high-performance mold made of age-hardenable copper alloy (beryllium copper 25 alloy) having complex water channels inside a laminated structure (FSW joint) of many thin plates using the FSW joint according to the present invention, and have succeeded in manufacturing an additive manufacturing body having a defect-free internal cooling water pipe.
[0020] Manufacturing method A preferred method for manufacturing an FSW joint according to the present invention will be described below. In this manufacturing method, first, (a) a metal member is placed on another metal member (step (a)). Next, (b) a tool is inserted into the other metal member and the metal member below it, and FSW is performed to join the metal member and the other metal member (step (b)). At this time, FSW is performed so as to disperse or break the oxide without leaving it in a layered state. (c) The surfaces of the metal members thus joined by FSW are removed by cutting to form a processed surface (joining surface) (step (c)). At this time, a shape (hole, recess, protrusion, etc.) for forming an internal structure or internal space of the FSW joint and / or a shape of the outer periphery may be given to the metal members 10 by cutting. Furthermore, (d) the above steps (a), (b) and (c) are repeated to manufacture an FSW joint (step (d)). At this time, step (a) is performed so that another metal member is placed on the processed surface. Finally, (e) the FSW joint thus obtained is subjected to solution aging treatment (step (e)).
[0021] (a) Stacking of metal components First, as shown in FIG. 1, another metal member 10 is placed on the metal member 10. As described above, each of the metal members 10 is preferably made of an age-hardenable copper alloy and / or an age-hardenable aluminum alloy. The thickness of the metal member 10 placed at the bottom is preferably 10 mm or more, more preferably 20 mm or more, and the upper limit is not particularly limited. That is, since the metal member 10 placed at the bottom does not need to be penetrated by the probe 6, it may be appropriately thickened as necessary. On the other hand, the thickness of another metal member 10 (i.e., the metal member of the second layer) placed on the metal member 10 at the bottom is not particularly limited as long as the probe 6 used can penetrate it, but is preferably 1.0 to 4.5 mm, more preferably 1.5 to 3.0 mm.
[0022] (b) Friction stir welding (FSW) Next, as shown in Fig. 1, a tool 2 (particularly a probe 6 at its tip) is inserted into another metal member 10 and the metal member 10 below it to perform FSW, thereby joining the metal member 10 and the other metal member 10. At this time, the FSW is performed so as to disperse or break the oxide without leaving it in a layered state. In this way, when the FSW joint is subjected to solution aging treatment, it is possible to avoid breakage at the joint and achieve strength equivalent to that of the base material.
[0023] As shown in Figs. 3 and 4, the tool 2 includes a cylindrical shank 4 and a probe 6 provided at the tip of the shank 4. The probe 6 is a tip portion for insertion into the metal member 10, and has a smaller diameter than the shank 4. The probe 6 is preferably configured so that the diameter of the probe 6 decreases continuously toward the tip. The tip diameter φa of the probe 6 is preferably 1.5 to 7.0 mm, more preferably 2.0 to 4.5 mm. The base diameter φb of the probe 6 is preferably 2.0 to 9.0 mm, more preferably 3.0 to 6.0 mm. The length c of the probe 6 is preferably 1.0 to 5.5 mm, more preferably 1.5 to 3.5 mm. The diameter φd of the shank 4 (shoulder) is preferably 5.0 to 25 mm, more preferably 6.0 to 18 mm. The probe 6 preferably has a groove 8, and the angle of the groove 8 (the angle that the groove 8 forms with respect to a plane perpendicular to the central axis of the probe 6) is preferably 2.0 to 6.5°, and more preferably 2.5 to 5.0°. The depth e of the groove 8 is preferably 0.1 to 0.6 mm, and more preferably 0.2 to 0.4 mm. The pitch f of the grooves 8 (the distance between adjacent grooves 8) is preferably 0.2 to 1.2 mm, and more preferably 0.3 to 1.0 mm.
[0024] In FSW, as shown in Fig. 1, while rotating the tool 2, a probe 6 is inserted into the joint 10a of the metal members 10 (base material), and the bottom surface (shoulder) of the shank 4 is slightly pressed in, which generates frictional heat to soften the base material, while the rotational force of the tool 2 causes plastic flow around the joint of the metal members 10 (base material) and kneads and mixes the metal members 10 together to integrate them. The tool 2 is then moved in a specified joining direction. At this time, the rotational speed of the tool 2 is 500 to 2000 min -1 is preferable, and more preferably 700 to 1800 min -1The insertion depth of the tool 2 into the metal member 10 is preferably 1.5 to 5.0 mm, and more preferably 2.0 to 3.5 mm. The joining speed of the tool 2 (i.e., the horizontal movement speed of the tool 2) is preferably 100 to 800 mm / min, and more preferably 100 to 600 mm / min. In addition, the FSW may be performed only once on the same location of the metal member 10 as long as the oxide can be dispersed or divided without leaving a layer-like oxide film, but by performing the FSW two or more times on the same location, the oxide can be dispersed or divided more effectively, and the layer-like oxide film can be more effectively eliminated.
[0025] (c) Cutting the top surface of the laminate The surface of the metal members 10 (the side where the probe 6 is inserted) joined by FSW is roughened by the FSW, and an oxide film is also formed. For this reason, the surface is removed by cutting to prepare a processed surface (joining surface). This processed surface is preferably a surface with improved flatness and cleanliness (i.e., smoother and cleaner). Cutting can be suitably performed by milling. The thickness of the surface removed by cutting (i.e., cutting depth) is not particularly limited as long as it is possible to remove one surface (the side where the probe 6 is inserted) of the metal members 10 over the entire surface so as to ensure the flatness of the processed surface, but is preferably 0.1 to 1.0 mm. In addition, the cutting is not limited to milling, and may be other techniques such as planing or surface grinding that can ensure the desired flatness and cleanliness after cutting. In this step (c), a shape (hole, recess, protrusion, etc.) and / or a peripheral shape for forming an internal structure or internal space of the FSW joint may be given to the metal members 10 by cutting. That is, by removing unnecessary portions of the placed separate metal member 10 (i.e., portions other than those to be left as a laminated structure) (see Patent Document 1), a laminated structure of the desired shape can be produced through the subsequent step (d) (i.e., repetition of steps (a) to (c)).
[0026] (d) Repeat steps (a) to (c). The above-mentioned steps (a), (b) and (c) are repeated to manufacture the FSW joint 12. At this time, step (a) is performed so that another metal member 10 is placed on the above-mentioned processing surface. Since this processing surface is preferably improved in flatness and cleanliness, the newly placed metal member 10 and the topmost metal member 10 joined by FSW can be joined by FSW in a highly desirable state. This allows additive manufacturing to be performed in a desirable manner, and the FSW joint 12 can be obtained as a laminated structure. The other metal member 10 further placed in this step (i.e., the metal member of the third layer or later) is typically a metal member of the same material and / or thickness as the metal member of the second layer, but may be a metal member of a different material and / or thickness. In any case, as described above, the metal member 10 laminated here is also preferably composed of an age-hardenable alloy (for example, an age-hardenable copper alloy and / or an age-hardenable aluminum alloy), and its thickness is not particularly limited as long as it is a thickness that can be penetrated by the probe 6 used, as described above, and is preferably 1.0 to 4.5 mm, and more preferably 1.5 to 3.0 mm. The number of times steps (a), (b), and (c) are repeated is not particularly limited as long as it is at least once, and may be 10 times or more, 50 times or more, or 100 times or more.
[0027] (e) Solution aging treatment The obtained FSW joint is subjected to solution aging treatment. Age hardening alloys can exhibit desired tempering characteristics (e.g., high strength) by undergoing solution and aging treatments. In the FSW joint of the present invention described above, even in solution aging treatment, the joint of the metal members is not damaged, and the joint after solution aging treatment has a strength equal to or greater than the strength of the base material of the metal members. The solution aging treatment is performed by (d1) subjecting the FSW joint to solution treatment and then (d2) subjecting it to aging treatment.
[0028] (e1) Solution treatment The FSW joint is subjected to a solution treatment. The solution treatment may be performed under known conditions according to the material of the metal members used. For example, when the FSW joint is made of an age-hardenable copper alloy, particularly C1720 as specified in JIS H 3130 or JIS H 3270, the solution treatment is preferably performed by heating the FSW joint at a temperature of 700 to 830°C for 1 to 180 minutes in a furnace such as an atmospheric furnace, a non-oxidizing atmosphere furnace, or a salt bath furnace, and then cooling with water. The solution treatment temperature is preferably 700 to 830°C, more preferably 740 to 800°C. The actual holding time at the above solution treatment temperature is preferably 1 to 180 minutes, more preferably 5 to 90 minutes, and even more preferably 5 to 30 minutes. Since the appropriate range of these solution temperatures varies depending on the alloy composition, it is desirable to select the optimal value with reference to a phase diagram or technical literature. The appropriate actual holding time at the solution treatment temperature does not differ significantly from the above.
[0029] On the other hand, when the FSW joint is made of an age-hardenable aluminum alloy, particularly A7075 as specified by JIS H 4040, the solution treatment is preferably performed by heating the FSW joint at a temperature of 460 to 500 ° C for 10 to 300 minutes in a furnace such as an atmospheric furnace, a non-oxidizing atmosphere furnace, or a salt bath furnace, and then cooling with water. The solution treatment temperature varies in a suitable range depending on the thickness of the joint, but is preferably 460 to 500 ° C, and more preferably 460 to 475 ° C. The actual holding time at the above solution treatment temperature is, for example, 120 to 190 minutes for a joint with a thickness of 50 mm, 150 to 220 minutes for a joint with a thickness of 75 mm, and 180 to 280 minutes for a joint with a thickness of 100 mm. Since the suitable range of these solution temperatures varies depending on the alloy composition, it is desirable to select the optimum value with reference to a phase diagram or technical literature.
[0030] (e2) Ageing treatment The solution-treated FSW joint is then subjected to aging treatment. The aging treatment may be performed under known conditions according to the material of the metal members used. For example, when the FSW joint is made of an age-hardenable copper alloy, particularly C1720 as specified in JIS H 3130 or JIS H 3270, the aging treatment is preferably performed at 280 to 340°C for 30 to 480 minutes. The aging treatment temperature is preferably 300 to 330°C, more preferably 310 to 320°C. The holding time at the aging treatment temperature is preferably 30 to 480 minutes, more preferably 30 to 300 minutes, even more preferably 60 to 240 minutes, and particularly preferably 90 to 180 minutes. From the viewpoint of suppressing oxidation, the aging treatment is performed at a temperature of 1.0×10 -1 A vacuum level higher than Torr (i.e. 1.0×10 -1 It is preferable to carry out the process in a furnace under a pressure lower than 100 Torr) or a non-oxidizing atmosphere such as nitrogen.
[0031] On the other hand, when the FSW joint is made of an age-hardenable aluminum alloy, particularly A7075 as specified in JIS H 4040, the aging treatment is preferably carried out at 116 to 127°C for 22 to 168 hours, more preferably at 116 to 127°C for 22 to 48 hours. EXAMPLES
[0032] The present invention will now be further illustrated by the following examples.
[0033] Examples A1 to A13 (1) Preparation of FSW joint The following two types of plates were prepared for each example. Laminated base (thick plate): 20mm thick beryllium copper 25 alloy plate (JIS H 3130 C1720-O) (one plate used at the bottom) Laminated material (thin plate): 2.0 mm thick beryllium copper 25 alloy plate (C1720-O of JIS H 3130) (used for all layers except the bottom layer)
[0034] Meanwhile, an FSW joining device as shown in Fig. 2 was prepared. This device was equipped with a stage on which the lamination base and lamination materials were placed, and an FSW tool that was placed above the stage and was movable in the vertical and horizontal directions. An FSW tool (type B) with the shape and dimensions shown in Table 1 and Fig. 3 was used. Fig. 3 shows the FSW tool 2, and Figs. 4, 5A, and 5B show photographs of the FSW tool 2. As shown in Figs. 3 and 4, the FSW tool 2 is composed of a shank 4 and a probe 6, and is fixed to the lower part of the holder 1.
[0035] [Table 1]
[0036] As shown in FIG. 2, a laminate base (thick plate) was placed on the table of the FSW welding machine, and a laminate material (thin plate) was placed on it. The FSW tool probe was inserted into the thin plate and the thick plate below it under the conditions of the tool shape, tool rotation speed, welding speed, and insertion depth, and insertion speed: 15 mm / min shown in Table 2, and the FSW was performed by moving the FSW tool horizontally along a specified path while stirring the area near the probe. At this time, as partially shown in FIG. 6, the FSW tool 2 was rotated while moving horizontally along a path P that drew lines spaced at equal intervals (3.0 mm) in a single stroke, forming a region R from which a test piece could be taken. This FSW was performed the number of times (one or two times) shown in Table 2 for the same location. After that, a part equivalent to a thickness of 0.3 mm was cut from the top surface of the welded thin plate over the entire surface to form a processed surface (welding surface), and as a result, an alloy layer with a thickness of 1.7 mm was laminated. A lamination material (thin plate) was further placed on the processed surface of the obtained laminate, and FSW and cutting were performed in the same manner as above, resulting in an alloy layer of 1.7 mm in thickness being further laminated. This lamination was repeated until the height of the laminate reached 80 mm, producing an FSW joint 12 as shown in Figure 7.
[0037] (2) Solution aging treatment In Examples A1 to A13 (beryllium copper 25 alloy), the FSW joint obtained in (1) above was held in a non-oxidizing atmosphere furnace at 800°C for 180 minutes, and then water-cooled to perform solution treatment. -2 The specimens were placed in a vacuum furnace at a vacuum level of 10 Torr at 320° C. for 3 hours, and then cooled in the furnace for aging treatment, thereby obtaining FSW joints that had been tempered by solution treatment and aging treatment.
[0038] (3) Evaluation of FSW joints The FSW joints obtained in (1) or (2) above were subjected to the following evaluations.
[0039] <Residual voids at the bonded interface> The FSW joints obtained in (1) above before solution aging treatment were cut perpendicular to the joint surface, and the presence of voids at the joint interface was evaluated by a dye penetrant test described in JIS Z 2343-1 "Nondestructive testing - Penetrant testing." As a result, no voids were found in the joints in any of the examples A1 to A13.
[0040] <Remaining oxide film> The cross section of the FSW joint before solution aging treatment obtained in (1) above was cut out and mirror polished, and then flat ion milling was performed with Ar ions to obtain an observation cross section. The obtained observation cross section was observed with a SEM (scanning electron microscope), and the cross section was subjected to elemental analysis with an EPMA (electron probe microanalyzer, product name: JXA-8530FPlus, manufactured by JEOL Ltd.) at an accelerating voltage of 15 kV to obtain an oxygen mapping. The obtained cross-sectional SEM image was compared with the oxygen mapping image to evaluate the remaining state of the oxide film according to the following criteria. In the following evaluation, "remaining layered oxide film" means that pixels showing a locally higher oxygen concentration than the surroundings are observed as stripes with a length of 10 μm or more. (Evaluation Criteria) - Evaluation A: No layer of oxide film was found remaining on the joint. - Evaluation B: A layer of oxide film was found to remain in some areas of the joint. - Rating C: A continuous layer of oxide film was found to remain at the joint.
[0041] The evaluation results were as shown in Table 2. Figures 8A and 8B show cross-sectional SEM images of Example A2 (Comparative Example) and oxygen mapping images of the corresponding regions, respectively, while Figures 9A and 9B show cross-sectional SEM images of Example A8 (Example) and oxygen mapping images of the corresponding regions, respectively. In these figures, the arrows point to the joint 10a. For Example A2, which is a comparative example, black streaks are observed at the joint 10a in Figure 8A, and by comparing the black streaks with the streaks of high oxygen concentration at the same position shown in the oxygen mapping of Figure 8B, it was confirmed that the black streaks at the joint 10a are oxide films, that is, a continuous layered oxide film remains. On the other hand, for Example A8, which is an example, black streaks are not observed at the joint 10a in Figure 9A, and no streaks of high oxygen concentration are observed in the oxygen mapping of Figure 9B, so it was confirmed that no layered oxide film remains at the joint 10a (i.e., the oxide is dispersed or divided).
[0042] <Tensile strength after solution aging> As shown in FIG. 7, a rod-shaped test piece S was cut out perpendicularly to the joint 10a (joint surface) between the metal members 10 (thin plates) from the FSW joint 12 after the solution aging treatment obtained in (2) above, and processed into the shape and dimensions (units in mm in the figure) shown in FIG. 7. In this way, a test piece S conforming to ASTM E8 Specimen 4 was obtained, in which the joint 10a exists in the parallel part (a part having the same cross-sectional dimensions in the center of the test piece S) and one of the gripping parts. The presence or absence of damage to the joint in the obtained test piece S was confirmed. A tensile test was performed on this test piece S at room temperature in accordance with ASTM E8, and the tensile strength (joint strength) was measured and evaluated according to the following criteria. The results were as shown in Table 2. (Evaluation Criteria) - Rating A: No damage was observed at the joints of the test specimens, and in the tensile test, all joints showed a tensile strength equal to or greater than the base material tensile strength of the beryllium copper 25 alloy (standard value 1100 MPa). - Rating C: Damage to the joints was observed in the test specimens, and in the tensile test, one of the joint layers broke below the tensile strength of the base material of the beryllium copper 25 alloy (standard value 1100 MPa).
[0043] As can be seen from the results shown in Table 2, in Examples A1 to A5, A12, and A13, where a layered oxide film was found to remain at the joint, the joint broke during solution aging, and in the tensile test, some of the joints showed a tensile strength inferior to the tensile strength of the base material. In contrast, in Examples A6 to A11, where no layered oxide film was found to remain at the joint, the joint did not break even after solution aging, and all of the joints showed a tensile strength equal to or greater than the tensile strength of the base material in the tensile test. [Table 2]
[0044] Examples B1~B6 (1) Preparation of FSW joint The following two types of plates were prepared for each example. Laminated base (thick plate): 20mm thick extra super duralumin plate (JIS H 4000 A7075) (used for the bottom layer), Laminated material (thin plate): 2.0 mm thick super duralumin plate (JIS H 4000 A7075) (used for all layers except the bottom layer)
[0045] On the other hand, an FSW joining device as shown in FIG. 2 was prepared. This device is equipped with a stage on which the lamination base and lamination materials are placed, and an FSW tool that is arranged above the stage and can move vertically and horizontally. Two types of FSW tools (types A and B) with shapes and dimensions shown in Table 3 and FIG. 3 were prepared, and one of them was selected and used in each example as shown in Table 4. FIG. 3 shows a schematic diagram of the FSW tool 2, and FIGS. 4, 5A, and 5B show photographs of the FSW tool 2. As shown in FIGS. 3 and 4, the FSW tool 2 is composed of a shank 4 and a probe 6, and is fixed to the lower part of the holder 1.
[0046] [Table 3]
[0047] As shown in FIG. 2, a laminate base (thick plate) was placed on the table of the FSW welding machine, and a laminate material (thin plate) was placed on it. The FSW tool probe was inserted into the thin plate and the thick plate below it under the conditions of the tool shape, tool rotation speed, welding speed and insertion depth, and insertion speed: 15 mm / min shown in Table 4, and the FSW was performed by moving the FSW tool horizontally along a specified path while stirring the area near the probe. At this time, as partially shown in FIG. 6, the FSW tool 2 was rotated while moving horizontally along a path P that drew lines spaced at equal intervals (3.0 mm) in a single stroke, forming an area R from which a test piece could be taken. This FSW was performed the number of times (one or two times) shown in Table 4 for the same location. After that, a portion equivalent to a thickness of 0.3 mm was cut from the top surface of the welded thin plate over the entire surface, resulting in an alloy layer with a thickness of 1.7 mm. A lamination material (thin plate) was further placed on the obtained laminate, and FSW and cutting were performed in the same manner as above, resulting in an alloy layer having a thickness of 1.7 mm. This lamination was repeated until the height of the laminate reached 75 mm, producing an FSW joint 12 as shown in Figure 7.
[0048] (2) Solution aging treatment The FSW joint obtained in (1) above was subjected to solution treatment by holding it in a non-oxidizing atmosphere furnace at 465°C for 200 minutes and then water-cooling. -2 The specimens were kept in a vacuum furnace at 120°C for 24 hours at a vacuum level of 1 Torr, and then cooled in the furnace for aging treatment, thereby obtaining FSW joints that had been tempered by solution treatment and aging treatment.
[0049] (3) Evaluation of FSW joints The FSW joints obtained in (1) or (2) above were subjected to the following evaluations.
[0050] <Residual voids at the bonded interface> The FSW joints obtained in (1) above before solution aging treatment were cut perpendicular to the joint surface, and the presence of voids at the joint interface was evaluated by a dye penetrant test described in JIS Z 2343-1 "Nondestructive testing - Penetrant testing." As a result, no voids were found in the joints in any of the examples B1 to B6.
[0051] <Remaining oxide film> For the FSW joints obtained in (1) above before solution aging treatment, cross-sectional SEM images and oxygen mapping images were obtained in the same manner as in Examples A1 to A13, and the remaining state of the oxide film was evaluated according to the following criteria. In the following evaluation, "remaining layered oxide film" means that pixels showing a locally higher oxygen concentration than the surroundings are observed as stripes with a length of 10 μm or more. (Evaluation Criteria) - Evaluation A: No layer of oxide film was found remaining on the joint. - Evaluation B: A layer of oxide film was found to remain in some areas of the joint. - Rating C: A continuous layer of oxide film was found to remain at the joint.
[0052] The evaluation results were as shown in Table 4. Figures 10A and 10B show cross-sectional SEM images and oxygen mapping images of the corresponding regions obtained in Example B1 (Comparative Example), respectively, while Figures 11A and 11B show cross-sectional SEM images and oxygen mapping images of the corresponding regions obtained in Example B6 (Example), respectively. In these figures, the arrows point to the joint 10a. In Example B1, which is a comparative example, black streaks were observed in the joint 10a in Figure 10A, and by comparing this with the streaks of high oxygen concentration at the same position shown in the oxygen mapping in Figure 10B, it was confirmed that the black streaks in the joint 10a were oxide films, that is, that a continuous layered oxide film remained. On the other hand, for Example B6, which is an embodiment, no black streaks are observed at the joint 10a in FIG. 11A, and no streaks of high oxygen concentration are observed in the oxygen mapping of FIG. 11B. This confirms that no layered oxide coating remains at the joint 10a (i.e., the oxide is dispersed or fragmented).
[0053] <Tensile strength after solution aging> Test pieces S were taken from the FSW joints 12 after the solution aging treatment obtained in (2) above in the same manner as in Examples A1 to A13, and the tensile strength (joint strength) was measured and evaluated according to the following criteria. The results are shown in Table 4. (Evaluation Criteria) - Rating A: No damage was observed at the joints of the test pieces, and in the tensile test, all joints demonstrated a tensile strength equal to or greater than the tensile strength of the extra super duralumin base material (standard value 360 MPa). - Rating C: Damage to the joints was observed in the test specimens, and in the tensile test, one of the joint layers broke below the tensile strength of the extra super duralumin base material (standard value 360 MPa).
[0054] For reference, the tensile strength standards stipulated in JIS H 4000 A 7075 are stipulated as follows, depending on the plate thickness: 360 MPa or more (plate thickness over 120 mm and not more than 300 mm), 410 MPa or more (plate thickness over 100 mm and not more than 120 mm), 460 MPa or more (plate thickness over 90 mm and not more than 100 mm), 490 MPa or more (plate thickness over 80 mm and not more than 90 mm), and 495 MPa or more (plate thickness over 60 mm and not more than 80 mm).
[0055] As can be seen from the results shown in Table 4, in Example B1, where a layered oxide film was found to remain at the joint, the joint broke during solution aging, and in the tensile test, some of the joints showed a tensile strength inferior to the tensile strength of the base material. In contrast, in Examples B2 to B6, where no layered oxide film was found to remain at the joint, no breakage occurred at the joint even after solution aging, and in the tensile test, all of the joints showed a tensile strength equal to or greater than the tensile strength of the base material.
[0056] [Table 4]
[0057] Examples C1 and C2 (1) Preparation of FSW joint The following two types of plates were prepared for each example. Laminated base (thick plate): 20 mm thick beryllium copper 11 alloy plate (JIS H 3130 C1751) (used for the bottom layer), Laminated material (thin plate): 2.0 mm thick beryllium copper 11 alloy plate (JIS H 3130 C1751) (used for all layers except the bottom layer)
[0058] On the other hand, similarly to Examples A1 to A13, an FSW joining apparatus as shown in FIG. 2 was prepared, and an FSW joining was performed as follows using an FSW tool (type B) having the shape and dimensions shown in Table 1 and FIG.
[0059] As shown in Figure 2, a laminate base (thick plate) was placed on the table of the FSW welding machine, and a laminate material (thin plate) was placed on it. The FSW tool probe was inserted into the thin plate and the thick plate below it under the conditions of the tool shape, tool rotation speed, welding speed and insertion depth, and insertion speed: 15 mm / min shown in Table 5, and the FSW was performed by moving the FSW tool horizontally along a specified path while stirring the area near the probe. At this time, as partially shown in Figure 6, the FSW tool 2 was rotated while moving horizontally along a path P that drew lines spaced at equal intervals (3.0 mm) in a single stroke, forming an area R from which a test piece could be taken. This FSW was performed twice at the same location. After that, a part equivalent to a thickness of 0.3 mm was cut from the top surface of the welded thin plate over the entire surface to form a processed surface (welding surface), and as a result, an alloy layer with a thickness of 1.7 mm was laminated. A lamination material (thin plate) was further placed on the processed surface of the obtained laminate, and FSW and cutting were performed in the same manner as above, resulting in an alloy layer of 1.7 mm in thickness being further laminated. This lamination was repeated until the height of the laminate reached 62.5 mm, producing an FSW joint 12 as shown in Figure 7.
[0060] (2) Solution aging treatment In the case of Examples C1 and C2 (beryllium copper 11 alloy), the FSW joint obtained in (1) above was held in a non-oxidizing atmosphere furnace at 900°C for 90 minutes, and then water-cooled to perform solution treatment. -2The specimens were placed in a vacuum furnace at a vacuum level of 100 Torr at 450° C. for 3 hours, and then cooled in the furnace for aging treatment, thereby obtaining FSW joints that had been refined by solution treatment and aging treatment.
[0061] (3) Evaluation of FSW joints The FSW joints obtained in (1) or (2) above were subjected to the following evaluations.
[0062] <Residual voids at the bonded interface> The FSW joints before solution aging treatment obtained in (1) above were cut perpendicular to the joint surface, and the remaining voids at the joint interface were evaluated according to the following criteria using a dye penetrant test described in JIS Z 2343-1 "Nondestructive testing - Penetrant testing". (Evaluation Criteria) - Rating A: No voids were found remaining in the joint. - Rating C: Voids were found remaining in the joint.
[0063] <Remaining oxide film> For the FSW joints obtained in (1) above before solution aging treatment, cross-sectional SEM images and oxygen mapping images were obtained in the same manner as in Examples A1 to A13, and the remaining state of the oxide film was evaluated according to the following criteria. (Evaluation Criteria) - Evaluation A: No layer of oxide film was found remaining on the joint. - Evaluation B: A layer of oxide film was found to remain in some areas of the joint. - Rating C: A continuous layer of oxide film was found to remain at the joint.
[0064] The evaluation results were as shown in Table 5. Figures 12A and 12B show cross-sectional SEM images and oxygen mapping images of the corresponding regions obtained in Example C1 (Comparative Example), while Figures 13A and 13B show cross-sectional SEM images and oxygen mapping images of the corresponding regions obtained in Example C2 (Example). In these figures, the arrows point to the joint 10a. In Example C1, which is a comparative example, black streaks were observed in the joint 10a in Figure 12A, and by comparing this with the streaks of high oxygen concentration at the same position shown in the oxygen mapping in Figure 12B, it was confirmed that the black streaks in the joint 10a were oxide films, that is, that a continuous layer of oxide film remained. On the other hand, for Example C2, which is an embodiment, no black streaks are observed at the joint 10a in FIG. 13A, and no streaks of high oxygen concentration are observed in the oxygen mapping of FIG. 13B. This confirms that no layered oxide coating remains at the joint 10a (i.e., the oxide is dispersed or fragmented).
[0065] <Tensile strength after solution aging> Test pieces S were taken and processed from the FSW joints 12 after the solution aging treatment obtained in (2) above in the same manner as in Examples A1 to A13, and the tensile strength (joint strength) was measured and evaluated according to the following criteria. The results are shown in Table 5. (Evaluation Criteria) - Rating A: No damage was observed at the joints of the test specimens, and in the tensile test, all joints showed a tensile strength equal to or greater than the base material tensile strength of the beryllium copper 11 alloy (standard value 690 MPa). - Rating C: Damage to the joints was observed in the test specimens, and in the tensile test, one of the joint layers broke below the tensile strength of the base material of the beryllium copper 11 alloy (standard value 690 MPa).
[0066] As can be seen from the results shown in Table 5, in example C1, where residual layered oxide films or voids were found in the joints, the joints broke during solution aging, and in the tensile test, some of the joints showed tensile strengths inferior to the tensile strength of the base material. In contrast, in example C2, where residual layered oxide films or voids were not found in the joints, the joints did not break even after solution aging, and all of the joints showed tensile strengths equal to or greater than the tensile strength of the base material in the tensile test.
[0067] [Table 5] [Explanation of symbols]
[0068] 1 Holder 2 Tools 4 Shank 6 Probe 8 grooves 10 Metallic parts (base material) 10a joint 12 FSW joint S test piece P pathway R region
Claims
1. A FSW joint in which a plurality of metal members are joined together by friction stir welding (FSW), wherein oxides that may remain after FSW are dispersed or separated inside the FSW joint without remaining in a layer form.
2. The FSW joint according to claim 1 , wherein the plurality of metal members are joined to one another without leaving any voids at the joint interface.
3. 2. The FSW joint of claim 1, wherein the FSW joint is to be subjected to a solution aging treatment.
4. The FSW joint of claim 1 , wherein each of the plurality of metallic members is comprised of an age hardenable alloy.
5. 5. The FSW joint of claim 4, wherein the age hardenable alloy is an age hardenable copper alloy and / or an age hardenable aluminum alloy.
6. The FSW joint according to any one of claims 1 to 5, wherein even when subjected to solution aging treatment, the joint of the metal members does not break, and the joint has a strength equal to or greater than the base material strength of the metal members.
7. 7. The FSW joint according to claim 6, wherein the metal members are made of beryllium copper 25 alloy (JIS H 3130 and C1720 of JIS H 3270), and the tensile strength of the joint and base material of the metal members when subjected to solution aging treatment is 1100 MPa or more.
8. 7. The FSW joint according to claim 6, wherein the metal members are made of beryllium copper 11 alloy (C1751 of JIS H 3130), and the tensile strength of the joint and base material of the metal members when subjected to solution aging treatment is 690 MPa or more.
9. 7. The FSW joint according to claim 6, wherein the metal members are made of extra super duralumin (A7075 of JIS H 4000), and the tensile strength of the joint and base material of the metal members when subjected to solution aging treatment is 330 MPa or more.
10. 7. The FSW joint according to claim 6, wherein the metal members are made of extra super duralumin (A7075 of JIS H 4000), and the tensile strength of the joint and base material of the metal members when subjected to solution aging treatment is 495 MPa or more.
11. The FSW joint according to any one of claims 1 to 5, further comprising an internal space as a cooling path inside the FSW joint.
12. A method for manufacturing an FSW joint in which a plurality of metal members are joined together by friction stir welding (FSW), comprising the steps of: (a) placing a metal member on another metal member; (b) a step of inserting a tool into the other metal member and the metal member underneath the other metal member and performing FSW to join the metal member and the other metal member, the FSW being performed in such a way that oxides are dispersed or separated without remaining in a layer; (c) removing the surfaces of the metal members joined by the FSW by cutting to form a machined surface; (d) repeating steps (a), (b) and (c) to produce a FSW joint, wherein step (a) is performed such that another metal member is placed on the work surface; and (e) subjecting the FSW joint to a solution aging treatment; A method for producing an FSW joint, comprising:
13. The method of claim 12 wherein each of the metallic members is comprised of an age hardenable alloy.
14. The method for producing an FSW joint according to claim 13, wherein the age hardenable alloy is an age hardenable copper alloy and / or an age hardenable aluminum alloy.
15. The manufacturing method of the FSW joint according to any one of claims 12 to 14, wherein the joint of the metal members is not broken during the solution aging treatment, and the joint after the solution aging treatment has a strength equal to or greater than the base material strength of the metal members.
Citation Information
Patent Citations
Frictional agitation joining device, frictional agitation joining tool and frictional agitation joining structure
JP2000153374A
Friction Spot Welding and Friction Seam Welding
US20150360317A1
Sheet metal blank and assembly with oxide removal zone
US20210283711A1
Layered manufacturing method and layered manufacturing device
JP6587028B1
